Fast charge transfer between iodide ions and a delocalized electron system on the graphite surface for boosting hydrogen production. Issue 45 (19th October 2022) - Peng, Shih-Mao; Patil, Shivaraj B.; Chang, Chun-Chih; Chang, Shu-Ting; Chen, Yi-Chia; Wu, Kuan-Chang; Su, Wei-Nien; Hwang, Bing Joe; Wang, Di-Yan
Abstract : The graphite-based materials with a delocalized π electron system exhibited fast charge transfer with physically adsorbed iodide ions, thus revealing desirable IOR catalytic activity. Abstract : Developing new catalysts to reduce the energy barrier for hydrogen production from water splitting has been an important research topic. It is well-known that the water-splitting voltage is limited by a theoretical potential of 1.23 V of the oxygen evolution reaction (OER). Recently, a new electrolytic method using the iodide oxidation reaction (IOR) instead of the OER has been proposed to produce the valuable chemicals iodine and hydrogen efficiently with a reduced operating voltage. In this work, we found that the graphite-based materials with a delocalized π electron system exhibited fast charge transfer with physically adsorbed iodide ions, thus revealing desirable IOR catalytic activity. The carbon fiber paper with a graphite structure was chosen as the catalyst and exhibited an onset potential of 0.54 V ( vs. RHE) for the IOR, which is close to the standard potential of iodide oxidation. Also, the CFP demonstrated a minimum Tafel slope of 47.78 mV dec −1 in the electrochemical reaction with significant stability at a current density of 10 mA cm −2 for over 18 hours. Moreover, in a two-electrode system, a cell voltage of only 0.59 V was required to provide a current density of 10 mA cm −2 for the IOR and hydrogen evolution reaction (HER). In terms of energy costs, our HER and IOR system can reduce energy consumption by 65% compared to conventional OER-based water electrolysis. The overall results indicate that our findings provide a new route to facilitate the industrial application of hydrogen production via electrochemical reactions.